2022
DOI: 10.3389/fphar.2022.870347
|View full text |Cite
|
Sign up to set email alerts
|

Active Tumor-Targeting Nano-formulations Containing Simvastatin and Doxorubicin Inhibit Melanoma Growth and Angiogenesis

Abstract: Primary melanoma aggressiveness is determined by rapid selection and growth of cellular clones resistant to conventional treatments, resulting in metastasis and recurrence. In addition, a reprogrammed tumor-immune microenvironment supports melanoma progression and response to therapy. There is an urgent need to develop selective and specific drug delivery strategies for modulating the interaction between cancer cells and immune cells within the tumor microenvironment. This study proposes a novel combination th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
(109 reference statements)
0
6
0
Order By: Relevance
“…The total antioxidant capacity (TAC) in plasma was measured by a Trolox Equivalent Antioxidant Capacity (TEAC) Assay, a spectrophotometric method developed by Erel [ 53 ], and applied by several groups of researchers [ 27 , 47 , 54 ]. The principle of the method relies on the ability of antioxidants to decolorize the blue-green 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid radical cation (ABTS(*+)), depending on their concentrations and antioxidant capacities.…”
Section: Methodsmentioning
confidence: 99%
“…The total antioxidant capacity (TAC) in plasma was measured by a Trolox Equivalent Antioxidant Capacity (TEAC) Assay, a spectrophotometric method developed by Erel [ 53 ], and applied by several groups of researchers [ 27 , 47 , 54 ]. The principle of the method relies on the ability of antioxidants to decolorize the blue-green 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid radical cation (ABTS(*+)), depending on their concentrations and antioxidant capacities.…”
Section: Methodsmentioning
confidence: 99%
“…To keep the cells alive, Dulbecco’s modified Eagle’s medium was used. A high concentration of glucose with fetal bovine serum (10%), along with an antibiotic–antimycotic solution (1%), in a CO 2 (5%), O 2 (18–20%) atmosphere, at a fixed temperature (37 °C) in the CO 2 incubator was maintained, and it was sub-cultured every 2 days [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…PEG-EV-Dox ensures prolonged systemic circulation time, higher accumulation of Dox, and more powerful tumor targeting potential. (Patras et al, 2022) (Figure 1C). Their latest study proposed a combination therapy with simvastatin incorporated in IL-13-functionalized long-circulating liposomes (IL-13-LCL-SIM) based on PEG-EV-Dox to selectively target both tumor-associated macrophages and melanoma cells.…”
Section: Evs Based Chemotherapy For Melanomamentioning
confidence: 99%
“…Their latest study proposed a combination therapy with simvastatin incorporated in IL-13-functionalized long-circulating liposomes (IL-13-LCL-SIM) based on PEG-EV-Dox to selectively target both tumor-associated macrophages and melanoma cells. ( Negrea et al, 2022 ). The results demonstrated that sequential administration of IL-13-LCL-SIM and PEG-EV-Dox had the most potent antiproliferative effect on melanoma cells.…”
Section: Introductionmentioning
confidence: 99%